2022
DOI: 10.1007/s11606-022-07523-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Post-Acute Sequelae of SARS-CoV-2 (PASC) After Diagnosis of Symptomatic COVID-19 in the Inpatient and Outpatient Setting in a Diverse Cohort

Abstract: Background The incidence of persistent clinical symptoms and risk factors in Post-Acute Sequelae of SARS-CoV-2 (PASC) in diverse US cohorts is unclear. While there are a disproportionate share of COVID-19 deaths in older patients, ethnic minorities, and socially disadvantaged populations in the USA, little information is available on the association of these factors and PASC. Objective To evaluate the association of demographic and clinical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 22 publications
4
57
0
1
Order By: Relevance
“…There were several studies that showed symptom changes following vaccination, however they were mostly cross-sectional in nature and thus impossible to establish true causality, and thus excluded. Furthermore, long COVID characteristics and symptomatology are getting well established with global data (1, 5, 18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were several studies that showed symptom changes following vaccination, however they were mostly cross-sectional in nature and thus impossible to establish true causality, and thus excluded. Furthermore, long COVID characteristics and symptomatology are getting well established with global data (1, 5, 18).…”
Section: Discussionmentioning
confidence: 99%
“…Long COVID, also known as post-acute COVID sequalae or post-acute COVID-19 syndrome, is now recognized as a major concern following COVID-19 infections, and likely to cause significant global morbidity for many years to come (1,2). With global case numbers over 500 million and with a conservative prevalence of 20-30%, more than 100 million people could be affected by long COVID worldwide (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research examined a limited set of contextual and spatial risk factors for PASC. For example, one study examined the association between the Social Vulnerability Index (SVI) and PASC using a sample of 1,000 COVID-19 patients from a single health system and found no differences in the likelihood of PASC between patients with higher and lower levels of SVI (Yoo et al, 2022). As individuals are exposed to multiple disadvantaged contextual and spatial factors simultaneously, more research is warranted to examine the totality of the environment using COVID-19 patients from geographically diverse regions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LCS can occur no matter which SARS-CoV-2 virus variant has been involved, since there is no evidence yet that there are any differences in the subsequent development of LCS between beta and delta or the present omicron infections (Su et al, 2022). Currently there is no clear unified idea on the pathogenesis of these syndromes (Maltezou et al, 2021;Yoo et al, 2022;Zhao et al, 2022), but the general idea is emerging that these are principally vascular diseases; judging by aspects of the active SARS-CoV-2 viral infection of COVID-19 patients (Kalafatis, 2021;Lei et al, 2021;Ostergaard, 2021;Siddiqi et al, 2021) and elements of the subsequent LCS (Charfeddine et al, 2021;Christensen and Berg, 2021). In fact, brain single-photon emission-computed tomography in fourteen LCS Long COVID patients seen in family practice with severe neurocognitive problems demonstrated vascular encephalopathy that was thought due to persistent coagulation disorders (Jamoulle et al, 2021).…”
Section: Introduction To Long Covid Syndromesmentioning
confidence: 99%